Some data regarding scientific research from Universidad Distrital Francisco José de Caldas in Scopus database in 2023 - Montoya, Oscar Danilo (Ingeniería, 2023)
This number of the Ingeniería journal explores the participation of the researchers from Bogotá City in Colombia that selects our journal to present their contributions in different research areas of Engineering, which includes Industrial, Electrical, Electronic, Civil, Environmental, Agricultural, and Mechanical Engineering, among others.